Assessment of Heavy Metals (Cr, Cu, Pb, and Zn) Bioaccumulation and Translocation by Erigeron canadensis L. in Polluted Soil - Volodymyr Laptiev; Michelle Giltrap; Furong Tian; Nataliia Ryzhenko (Pollutants, 2024)
This work aims to assess the bioavailability and bioaccumulation of Cr, Cu, Pb, and Zn in the soil–plant system (Erigeron canadensis L.) in the zone of anthropogenic impact in Dnipro city, a significant industrial and economic centre of Ukraine. Sampling was carried out at three locations at distances of 1.0 km, 5.5 km, and 12.02 km from the main emission sources associated with battery production and processing plants in Dnipro. The concentrations of heavy metals such as Cr, Cu, Pb, and Zn were analysed using atomic emission spectrometry from soil and parts of Erigeron canadensis L. The highest concentrations of elements in the soil, both for the mobile form and the total form, were determined to be 48.96 mg kg−1 and 7830.0 mg kg−1, respectively, for Pb in experimental plot 1. The general ranking of accumulation of elements in all experimental plots, both for the plant as a whole and for its parts, was as follows: Zn > Cu > Cr > Pb. Zn for plants was the most available heavy metal among all studied sites and had the highest metal content in the plant (339.58 mg kg−1), plant uptake index (PUI-506.84), bioabsorption coefficient (BAC-314.9), and bioconcentration coefficient (BCF-191.94). According to the results of the study, it is possible to evaluate Erigeron canadensis L. as a hyperaccumulator of Zn, Cu, and Cr and recommend it for phytoextraction of soils contaminated with Zn, Cu, and Cr and phytostabilization of soils contaminated with Pb.